Global Internet Governance - Leong, Susan. author. aut Link
X, 105 p. 1 illus.
Keywords: 'Internet governance remains in crisis, without a clear roadmap for the future –– so where do we turn? This brilliant and timely new book by Susan Leong and Terence Lee urges us to look beyond the fixation with US or China, or multistakeholderism or multilateralism as the default options. They propose a ‘hybrid model’ as the way forward, showing how this has unfolded, warts and all, in the dynamic Southeast Asian region in the cases of Singapore and Malaysia. Their rich and persuasive account underscores the importance of understanding actually-existing Internet governance as the foundation to decolonising, debugging, and reforming Internet governance for all. This book is indispensable reading for anyone concerned about the crossroads in communication and technology governance and policy today.' — Professor Gerard Goggin, Nanyang Technological University, Singapore This book addresses the complex issue of global Internet governance by focusing on its implementation in Malaysia and Singapore. The authors draw insights, identify, revisit and flesh out the discourses circulating since the 1990s and pitch them against global Internet governance concerns. Readers of this book will understand how and why Malaysia and Singapore are important contributors to current concerns over Internet governance, provoked in part by China’s advocacy of internet sovereignty, and the American and global responses. Readers will also appreciate how and why the regulation of the Internet has been and will remain a site of contestation and control. Susan Leong is Senior Lecturer with Monash University Malaysia. She is the author of New Media and the Nation in Malaysia: Malaysianet (2014) and Culture, Technology and Platforms: Chinese Digital Presence in the Asia Pacific (forthcoming). Terence Lee is an Associate Professor in Communication and Media Studies and a Fellow of the Asia Research Centre at Murdoch University. He is the author/editor of several books including The Media, Cultural Control and Government in Singapore (2010), and Singapore: Negotiating State and Society, 1965-2015 (with Jason Lim, 2016).